Group Communication Predicts Student Politeness Ethics in Junior High School: Komunikasi Kelompok Memprediksi Etika Kesopanan Siswa di Sekolah Menengah Pertama - H Arief Wicaksono; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education supports the development of moral values, social ethics, and interpersonal behavior among students. Specific Background: Group communication in educational settings facilitates idea exchange, social interaction, and the internalization of respectful behavior among junior high school students. Knowledge Gap: Empirical measurement of the relationship between group communication and politeness ethics among seventh-grade students remains limited. Aims: This study analyzes the relationship between group communication and politeness ethics among seventh-grade students at SMPN 1 Sedati. Results: Using a quantitative approach with total sampling of 372 students, questionnaire and observation data analyzed through simple linear regression revealed a significant relationship between group communication and politeness ethics (p = 0.000 < 0.05), with a correlation value of 0.554 and a determination coefficient of 30.7%, represented by the regression equation Y = 18.704 + 0.631X. Novelty: This study presents empirical statistical evidence of the measurable contribution of group communication to student politeness ethics in a junior high school setting. Implications: The findings support incorporating structured group communication activities into character education programs to promote ethical behavior and positive social interaction in schools. Highlights: Peer Interaction Patterns Demonstrate a Moderate Statistical Association With Respectful Student Conduct. Social Interaction Contributes 30.7% to Behavioral Etiquette Formation. Collaborative Discussion Activities Support Moral Value Internalization Among Adolescents. Keywords: Group Communication, Politeness Ethics, Character Education, Student Behavior, Quantitative Regression